Comorbid alcohol and nicotine dependence: from the biomolecular basis to clinical consequences - Ait-Daoud, Nassima; Wiesbeck, Gerhard A.; Bienkowski, Przemyslaw; Li, Ming D.; Pfützer, Roland; Singer, Manfred V.; Lesch, Otto M.; Johnson, Bankole A. (Alcoholism, 2005)
This article represents the proceedings of a symposium presented at the 12th Congress of the International Society for Biomedical Research on Alcoholism held in Heidelberg/Mannheim, Germany, on October 1, 2004. The organizers and cochairs were Nassima Ait-Daoud, MD, and Gerhard A. Wiesbeck, MD. The presentations included the following: (1) The Role of Nicotinic Acetylcholine Receptors in Alcohol-Seeking Behavior, by Przemyslaw Bienkowski, MD, PhD; (2) Utilization of Linkage Analysis Combined with Microarray Technology to Identify Genes and Mechanisms Underlying Nicotine and Alcohol Use and Abuse in Humans and Rodents, by Ming D. Li, PhD; (3) Smoking and Alcoholic Chronic Pancreatitis: The Underestimated Risk?, by Roland H. Pfützer, MD; (4) Anticraving Medication in Alcohol and Nicotine Dependence, by Otto M. Lesch, MD, PhD; and (5) Pharmacotherapy for Promotion of Abstinence from Nicotine Among Alcohol-Dependent Individuals, by Bankole A. Johnson, DSc, MD, PhD.